Distribution patterns patterns and indicators of the smooth hammerhead shark (Sphyrna zygaena) in the Atlantic Ocean - Santos, Catarina C. (2020)
The smooth hammerhead shark, Sphyrna zygaena, is a pelagic shark occasionally captured as bycatch by industrial pelagic longline fleets in the Atlantic Ocean. Data for this study were collected by fishery observers, between 2003 and 2016. Datasets analyzed included information on catches per unit effort (CPUE), size and sex of smooth hammerhead sharks bycaught by the Portuguese pelagic longline fishery in the Atlantic Ocean. A total effort of 2 523 288 hooks yielded 638 sharks, ranging in size from 123 to 275 cm fork length. Larger sharks tended to occur in open ocean habitats and smaller specimens in coastal areas. Results confirmed the wide latitudinal range of the species (45 degrees N-35 degrees S), although CPUE was higher closer inshore within the Tropical North and Equatorial regions. An overall sex ratio of 1.4 males for each female was observed, with more males in both inshore and offshore waters. Significant differences in CPUE and size distribution were found between regions, years and quarters of the year. Mean CPUE increased and mean specimen size decreased in the Equatorial region from 2012 onwards. In order to remove fishery-dependent effects from CPUE data, a Tweedie Generalized Linear Model (GLM) was used to create a relative index of abundance (standardized CPUE). The index showed some oscillations in the initial years (2008-2010), followed by a decreasing trend until 2013 and then an increasing trend in more recent years, until 2016. The distributional patterns and indicators presented in this study provide a better understanding of the smooth hammerhead shark's spatio-temporal dynamics and population structure in the Atlantic Ocean and can be used to improve management and conservation measures for this species.